1999
DOI: 10.7164/antibiotics.52.730
|View full text |Cite
|
Sign up to set email alerts
|

Ala(0)-actagardine, a New Lantibiotic from Cultures of Actinoplanes liguriae ATCC 31048.

Abstract: The actagardine-producing strain Actinoplanes liguriae ATCC3 1048, forms an additional lantibiotic when it is cultured on mannitol and soya meal. The new compound, Ala(0)-actagardine (1), has been isolated by solid-phase extraction followed by a two-step chromatographic separation. The molecular formula of 1 is C84H129N21O25S4. Its chemical structure was determined by 2D-NMRanalysis and was further confirmed by an amino acid analysis, Edman degradation, and partial synthesis from actagardine. 1 exhibits a slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In this instance, cleavage between position −1 and −2 would result in the retention of an alanine residue at the N‐terminus, generating ala(0) variants (m/z +36 for doubly charged ions) of actagardine. Such variants were described by Vértesy et al . (1999) and are routinely observed in the fermentation broths of A. garbadinensis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this instance, cleavage between position −1 and −2 would result in the retention of an alanine residue at the N‐terminus, generating ala(0) variants (m/z +36 for doubly charged ions) of actagardine. Such variants were described by Vértesy et al . (1999) and are routinely observed in the fermentation broths of A. garbadinensis .…”
Section: Resultsmentioning
confidence: 99%
“…In this instance, cleavage between position -1 and -2 would result in the retention of an alanine residue at the N-terminus, generating ala(0) variants (m/z +36 for doubly charged ions) of actagardine. Such variants were described by Vértesy et al (1999) and are routinely observed in the fermentation broths of A. garbadinensis. The abundance of ala(0) products containing an additional N-terminal alanine residue appears to decrease in prolonged fermentations of A. garbadinensis presumably due to cleavage of the N-terminal alanine.…”
Section: Analysis Of the Cosmid Cosag14 Encoding The Biosynthetic Genmentioning
confidence: 94%
“…This modification has only been found in the 19-amino acid globular lanthipeptide actagardine (also known as gardimycin) 452 and Ala(0)-actagardine, which differs from actagardine by a single additional Ala residue at the N-terminus (Figure 42). 453 The structure of actagardine was determined by a combination of Edman sequencing, MS, and NMR analysis, 454456 revealing that oxidation occurs site-selectivity in the D-ring. 454 The genetic origin of sulfoxide formation was uncovered through a comparison of the gene clusters of actagardine and another lanthipeptide michiganin A, 86 which is similar in structure to actagardine but lacks the sulfoxide.…”
Section: Class II Lanthipeptide Biosynthesismentioning
confidence: 99%
“…7, 8 Ala(0)-actagardine is a natural variant with an additional N-terminal alanine that is produced by Actinoplanes liguriae ATCC 31048. 9 Actagardine possesses potent antimicrobial activity against gram-positive pathogens including Clostridium difficile and is stable in simulated gastric fluid. 10 Actagardine inhibits cell wall biosynthesis by binding to lipid II, 11 and its binding is not antagonized by vancomycin.…”
mentioning
confidence: 99%